RETHINKING NUSANTARA INDONESIA: LEGAL APPROACH - Buntoro, Kresno (Indonesian Journal of International Law, 2016)
As one of the proponents of the archipelagic State concept, Indonesia considers the archipelagic State regime as Nusantara. Indonesia believes that the waters surrounding the islands considered an integral part of the island and part of its State territory. However, Indonesia seem to realize that Nusantara has to adopt the international community interest such as providing sea lanes of communication and addressing the challenges ensuing from conducting activities within its waters and surrounding. These balances of interest stipulated in the provision of the United Nations Convention on the Law of the Sea 1982 (LOSC). Indonesia seems very satisfied when the archipelagic state concept has been adopted in the LOSC, but there are many issues exist when discussing the implementation of the Nusantara.